Novel type of plasmid-borne resistance to trimethoprim. - Sundström, L (1987)
A novel trait for transferable resistance to high concentrations of trimethoprim was found to dominate among enterobacteria collected from different parts of Sri Lanka. Drug resistance was a result of the production of dihydrofolate reductase with a decreased sensitivity to antifolates. By characterization of the partially purified enzyme and by restriction enzyme digestion analysis, the newly found gene was shown to be distinct from the earlier known plasmid-borne resistance genes which express dihydrofolate reductases of types I, II, and III. Cloning of fragments containing the resistance gene and further restriction enzyme digestion analysis showed that this gene was inserted very close to a sulfonamide resistance gene. Evolution of trimethoprim resistance in Sri Lanka thus seems to have taken a different route from that taken in the industrialized world, where transposon Tn7 seems to dominate. The close combination of the new trimethoprim resistance gene with sulfonamide resistance on the plasmids studied would effect an efficient spread of these genes, since trimethoprim has most often been used in combination with a sulfonamide.